Disentangling economic recessions and depressions - Bertrand Candelon; Norbert Metiu; Stefan Straetmans (Deutsche Bundesbank, 2013)
We propose a nonparametric test that distinguishes 'depressions' and 'booms' from ordinary recessions and expansions. Depressions and booms are defined as coming from another underlying process than recessions and expansions. We find four depressions and booms in the NBER business cycle between 1919 and 2009, including the Great Depression and the World War II boom. Our results suggest that the recent Great Recession does not qualify as a depression. Multinomial logistic regressions show that stock returns, output growth, and inflation exhibit predictive power for depressions. Surprisingly, the term spread is not a leading indicator of depressions, in contrast to recessions.
Keywords: C14; C35; E32; 330; Business cycles; Depression; Leading indicators; Multinomial logistic regression; Nonparametric statistics; Outlier